2023
DOI: 10.1097/tp.0000000000004391
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Spontaneous Portosystemic Shunts in Liver Transplantation: A Comprehensive Assessment Through Total Shunt Area Measurement

Abstract: Background. The impact of spontaneous portosystemic shunts (SPSSs) on natural history of cirrhotic patients was recently evaluated through the measurement of total shunt area (TSA), a novel tool that allows a comprehensive assessment of SPSSs extension, identifying a direct correlation of higher TSA with lower patient survival. The role of SPSSs in liver transplant (LT) is still debated: we sought to investigate the clinical impact of TSA on the development of early allograft dysfunction (EAD), acute kidney in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This presents a potential hazard of graft hypoperfusion, portal vein thrombosis, and impaired liver regeneration, attributable to the so-called steal phenomenon. 42 Given this context, we have advocated for a systematic approach to intraoperative/perioperative ligation of SPSSs to optimize portal flow to the liver allograft, thereby averting graft hypoperfusion and loss. 14 Tailoring portal hemodynamics becomes particularly crucial when managing a partial allograft with diminished vascular capacity, as this may impede SPSSs detention and exacerbate the portal steal phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This presents a potential hazard of graft hypoperfusion, portal vein thrombosis, and impaired liver regeneration, attributable to the so-called steal phenomenon. 42 Given this context, we have advocated for a systematic approach to intraoperative/perioperative ligation of SPSSs to optimize portal flow to the liver allograft, thereby averting graft hypoperfusion and loss. 14 Tailoring portal hemodynamics becomes particularly crucial when managing a partial allograft with diminished vascular capacity, as this may impede SPSSs detention and exacerbate the portal steal phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring a thorough assessment of graft perfusion is paramount when confronted with this “short blanket.” The current literature strongly advocates for comprehensive intraoperative flow-pressure monitoring to customize portal flow to the graft volume. 31,43 Centonze et al 42 have identified a higher total shunt area (measured in mm 3 ) as a noteworthy risk factor for unfavorable post-LT outcomes. This underscores the necessity for meticulous hemodynamic assessment and management in patients with multiple or larger shunts.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Second, pre-LT CTscan of the recipient allows for identifying surrogates of LPF, such as PVT, [27,28] portal vein caliber, [29] and PSS. Besides, pre-LT evaluation by CT-scan [30] or 4D-MRI [31] is a promising perspective to anticipate the surgical strategy for portal flow modulation by providing a precise anatomic and hemodynamic mapping of PSS. Second, in the case of high GRWR and potential LPF, recipients with portal hypertension, ascites, or PSS should be preferentially selected as they present the possibility of portal inflow modulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of large (>10 mm) shunts without PVT, the recipient hepatectomy becomes technically easier because of attenuated perihepatic collaterals. Also, previous studies have reported the presence of a large shunt as an independent risk factor for clinically relevant complications, grade 3 acute kidney injury (AKI), and even the development of early allograft dysfunction (EAD) after liver transplantation (LT) 5 . As the recipients with large shunts can skew the study outcomes, they were excluded.…”
Section: Methodsmentioning
confidence: 99%